Letter from J. Churchman to James Curtis Booth - Churchman, J. (1866)
J. Churchman, writing on behalf of his nephew, seeks advice on the best work on the subject of smelting ore of silver from James Curtis Booth (1810-1888). Booth notes his response on the document verso, "I recommend as fair Percy's Metallurgy and Mitchell on Assaying as the best Kerl's Metallurgy."
Keywords: Booth, James Curtis, 1810-1888; Smelting; Silver--Assaying; Metallurgy